Use of Explosives: Classification and Regulation - Bermana, Seftiandra Bermana; Hafizah, Mas Ayu Elita; Ruyat, Yayat; Rosyida, Esa Dina Inda (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Of the many qualifications of explosives, for some reason allowed for use by civilians. This study aims to analyze the classification and regulation of the use of explosives, using the literature study method. As a result, there are special rules from several institutions for the use of explosives in various fields.